Formulation of a sustainable financial management strategy for South African universities' hotel schools - Crowther, Dalene (Bloemfontein: Central University of Technology, Free State, 2018)
In recent years, the Central University of Technology, Free State (CUT) Hotel School has been nominated as Bloemfontein’s Business of the Year; internationally recognised as a leader in the field of education and training in the service industries; and regarded as “one of South Africa’s premier hotel schools”. The Hotel School finds it increasingly challenging to balance its income and expenses, and to function as a financially viable academic unit in a sustainable way. Reasons ascribed to these negative figures are the capped student intake, regulating the state-funded Teaching Input Grant and the tuition fees received; the relatively low lecturer-student ratio; relatively high operational costs; relatively high dropout rates, with a negative effect on the Actual Teaching Output Grant received from the state; unsatisfactory staff research outputs, negatively impacting on the state Actual Research Output Grant received; and third-stream income potential not being fully realised. National and international challenges in higher education, such as the continuously increasing demand for quality education, increased access rates, strong competition, deteriorating resource allocation, high dropout rates, poor knowledge production, and low success rates, are also faced by the CUT Hotel School. Innovative ways of generating income options must thus be identified in order to move towards a sustainable financial model. Therefore, the main aim of this study is to formulate a sustainable financial management strategy for South African universities’ hotel schools. The researcher employed a qualitative research design, using document analyses and one-to-one semi-structured interviews held at top international, as well as at South African universities’ hotel schools. The findings that were obtained were transcribed verbatim, coded and categorised into themes. The computer software programme Atlas.ti was also used to assist in data analysis. The main findings of this study indicated that an increase in Full-time Equivalent students (FTEs), an increase in research output, and an increase in teaching output are required to improve the financial sustainability of hotel schools. This can only be accomplished through the implementation of a proper hotel school marketing strategy, focused on promoting the academic offerings of the schools, short and online courses, as well as the operational facilities and services that hotel schools can offer, including the possible expansion of such services in an attempt to generate additional sources of third-stream income. A strong alumni and industry partner network needs to be built and maintained, as this will also assist in improving the financial sustainability of hotel schools. The findings of this study inform a sustainable financial management strategy for South African universities’ hotel schools.
Published Thesis